The Alteration and Significance of Erythropoietin Serum Levels in Preterm Infants with Retinopathy of Prematurity - Yang, Xiaofeng; Ze, Bi; Dai, Yi; Zhu, Li; Chen, Chao (American Journal of Perinatology, 2017)
Objective This study aims to investigate the changes of serum erythropoietin (EPO) in premature infants with retinopathy of prematurity (ROP) after birth.Method The premature infants were divided into two groups, the first were infants with ROP, and the rest were infants without ROP. The peripheral blood of these infants after birth was collected, aiming to identify the correlation of serum EPO with ROP in the first 8 weeks after birth and before 38 weeks' postconceptual age.Results A total of 299 infants without ROP and 107 infants with ROP were recruited into our study. It was suggested that serum the EPO level in ROP group was significantly lower than it is in the group without ROP on the 28th day after birth. The median value of serum EPO in the group with and without ROP at day 28 of life were 0.44 mIU/mL and 0.62 mIU/mL, respectively (p = 0.017). These data indicated that there was no significant association between serum EPO and the clinical factors. Multivariate analysis identified only EPO serum level on the 28th day after birth and gestational age as independent predictors of ROP (p was 0.025 and 0.021, respectively).Conclusion EPO serum level may serve as a surrogate marker for the development of ROP.
Keywords: retinopathy of prematurity; erythropoietin; serum levels; premature infants